Identification of Vibrio isolated from Mangrove Sediment Near to Vannamei Ponds - Ery Gusman (Samakia : Jurnal Ilmu Perikanan, 2019)
This study aims to identify the vibrio in mangrove forest areas near to the location of vannamei ponds, especially in sediment substrates. The research is at the Mangunharjo sub-district in the Mayangan District, Probolinggo City, East Java Province. The time of study is august and September 2019. Isolation of bacteria being done with total plate count procedure on Thio Sulfate Citrate Bile Sucrose (TCBS) Agar, with pour plate method. Morphology characterization and the biochemical test was done to identify the bacteria. There are three points of the sampling area, with each area distance from 100 to 500 meters. This location choosing based on purposive sampling method, which main reason is the site must have mangrove with good vegetation and variation. It is transected by 5m x 5m, 100-gram sediment at 30-40 cm depth taken randomly using sediment scoop. Three samples of each sampling area chosen randomly at three different locations, then mixed. The result showed each deposit from different sampling locations having bacteria colony with color are yellow, green, and green blueish. These colony of bacteria in this sediment suspected as v. harveyii, v. alginolyticus, v. fischery dan v. mimicus.